PERSEPSI SISWA TERHADAP ASSESSMENT FOR LEARNING DAN PENGARUHNYA TERHADAP MOTIVASI INTRINSIK SISWA: AUTONOMY, COMPETENCE DAN RELATEDNESS SEBAGAI VARIABEL MEDIASI - Restia Ayangsa; Dessi Susanti (Jurnal Muara Pendidikan, 2025)
This study aims to analyze students’ perceptions of assessment for learning and its effect on intrinsic motivation, with relatedness, competence, and autonomy as mediating variables. The background of this research is the low level of student learning motivation, which is suspected to be caused by the suboptimal fulfillment of basic psychological needs and the incomplete implementation of assessment for learning in the learning process. This study uses a quantitative approach with an associative method. The sample consisted of 183 eleventh-grade students from SMAN 2 Bungo, selected using proportional random sampling. Data were collected using a Likert-scale questionnaire and analyzed using the Structural Equation Modeling (SEM) model based on Partial Least Square (PLS). The results show that students’ perceptions of assessment for learning significantly influence their intrinsic motivation. This effect is significantly mediated by relatedness, competence, and autonomy. These findings emphasize that properly implemented formative assessment can help meet students’ basic psychological needs, thereby enhancing their internal motivation to learn. Therefore, teachers are encouraged to consistently apply assessment for learning in a way that fosters social connectedness, a sense of competence, and learner autonomy.